Nursing Research and Education: Goals Reached - María de los Ángeles Rodríguez Gázquez (Universidad de Antioquia, 2016)
Nursing Research and Education (IEE, for the term in Spanish) is a publication that has brought much satisfaction to the Faculty of Nursing at Universidad de Antioquia (Colombia) because of the goals reached during its 34 of edition. In my opinion, the most important achievement is that since 1983, it has published 879 articles without interruption and which have been compiled into 75 numbers. Another goal reached is improved visibility, which we have enhanced notably in the last decade. Specifically, we have confronted three challenges: the first has to do with increased number of articles received, which we have achieved by maintaining an on-line platform to facilitate submission and follow up of manuscripts; the journal’s shift from Spanish to English; and greater emphasis on the quality of the articles submitted to peer evaluation. This was how in 2015 we received 163 articles for consideration and of which 62 were accepted for publication.